Research into kinetic patterns of chemical metallization of powderlike polyvinylchloride - Moravskyi, Volodymyr; Dziaman, Iryna; Suberliak Sofiіa; Kuznetsova, Marta; Tsimbalista, Tatiana; Dulebova, Ludmila (Eastern-European Journal of Enterprise Technologies, 2017)
We present kinetic patterns of metallization of zinc-activated polyvinylchloride in the solution of chemical copper plating. The influence was studied of pH of the medium and the amount of metal of the activator on the copper deposition rate on the activated polymeric surface. It was established that in the case of activation of the polymeric surface with zinc, the solution undergoes two competing reactions of copper reduction. By using a volumetric method, we determined that pH of the medium exerts a decisive impact on the reduction mechanism of copper. It is proved that with the growth of pH in the solutions of chemical copper plating and the amount of metal-activator, the amount of copper reduced as a result of exchange reaction with zinc increases. The optimal pH of the solutions for the course of reaction of copper reduction by formaldehyde is 12. The obtained samples of metallized powder-like polyvinylchloride contain a significant quantity of copper on the surface and could be used to create metal-filled composites. The research conducted allows us to establish optimal conditions and effectively influence the copper reduction process on the activated polymeric surface in the solutions of chemical metallization. By changing the speed and efficiency of copper deposition on the polymeric surface, it is possible to control the content of metal in polymeric composites that are obtained from such materials, and thus control their properties